THE VALUE OF HUMAN LIFE IN THE ENCYCLICAL 'EVANGELIUM VITAE' BY JOHN PAUL II - Anna Laputko ("Scientific Information Agency "Science-technologies-information" LLC, 2021)
In the encyclical "Evangelium Vitae", Pope John Paul II bases his message on the Scriptures, as is customary in formulating the doctrine or moral compendium of the Christian church. Jesus Christ, the mystery of the incarnation of the Logos, is the basis for understanding the value of human life from conception to natural death. The encyclical reveals attempts to reduce the value of life, which includes war, violence, abuse of bioethical aspects (abortion, euthanasia).